Hydrochemical characteristics and seasonal variations in groundwater quality of an alluvial aquifer in parts of Central Ganga Plain, Western Uttar Pradesh, India - Mohammad Muqtada Ali Khan; Rashid Umar (2009)
The present study was undertaken to assess major ion chemistry of groundwater in parts of the Central Ganga Plain and observe seasonal variations in its chemical quality. Systematic sampling was carried out during November 2005 and June 2006. The major ion chemistry of groundwater shows large variations, so much so that at times the meteoric signature seems to be completely obliterated. In many samples the concentrations of SO4, NO3 and F are above the permissible limit for human consumption. The graphical treatment of major ion chemistry helps in identifying four types of groundwater. All possible ionic species such as NaCl, KCl, NaHCO3, NaSO4, KNO3, NaNO3, CaHCO3, MgHCO3, MgSO4 are likely to occur in groundwater system. The observed chemical variations may be attributed to sediment water interaction, ion exchange, dissolution mechanisms and anthropogenic influences such as application of fertilizers and effluents from sugar factories and paper mills. A general increase in TDS is observed in samples during June 2006. The increase in salinity is attributed to evaporation from water table, irrigation return flows, anthropogenic activities and below average rainfall in 2005 and 2006.